2017
DOI: 10.1080/2162402x.2016.1265719
|View full text |Cite
|
Sign up to set email alerts
|

High baseline levels of interleukin-8 in leukocytes and urine predict tumor recurrence in non-muscle invasive bladder cancer patients receiving bacillus Calmette–Guerin therapy: A long-term survival analysis

Abstract: (2017) High baseline levels of interleukin-8 in leukocytes and urine predict tumor recurrence in non-muscle invasive bladder cancer patients receiving bacillus Calmette-Guerin therapy: A long-term survival analysis, OncoImmunology, 6:2, e1265719,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 36 publications
0
10
1
Order By: Relevance
“…However, CXCL10 was not included in this study. Although IL-8 was previously studied as a potential biomarker of responsiveness when released in the initial hours after instillation [18,19,20], our data show a decrease in this cytokine over time in responder patients. Based on our results, a focused study in a larger cohort is being planned in order to test this hypothesis and validate the use of CXCL10 as a biomarker for response.…”
Section: Discussioncontrasting
confidence: 58%
“…However, CXCL10 was not included in this study. Although IL-8 was previously studied as a potential biomarker of responsiveness when released in the initial hours after instillation [18,19,20], our data show a decrease in this cytokine over time in responder patients. Based on our results, a focused study in a larger cohort is being planned in order to test this hypothesis and validate the use of CXCL10 as a biomarker for response.…”
Section: Discussioncontrasting
confidence: 58%
“…Therefore, European Association of Urology (EAU) Guidelines on NMIBC recommend intravesical BCG immunotherapy after TURBT in patients with intermediate-or high-risk NMIBC (1). Some studies have investigated the effect of intravesical BCG immunotherapy on some angiogenetic factors and cytokines such as interleukin (IL)-8 in patients with NMIBC (6,7). They suggested that these factors and cytokines might be used for the follow up after intravesical BCG immunotherapy in NMIBC.…”
Section: Resultsmentioning
confidence: 99%
“…Cytokines and chemokines have already been shown to be suitable for the detection and prediction of the BCG response. 12 Previous studies have developed multiple cytokine panels to predict the treatment response to BCG; however, they have limited clinical usefulness for the measurement techniques and costs . 4,13 In an attempt to identify a robust predictive biomarker for potential clinical use, we evaluated 48 cytokines and chemokines involved in several stages of the mechanism of BCG immunotherapy and screened the cytokine or chemokine with most predictive value.…”
Section: Discussionmentioning
confidence: 99%